1990
DOI: 10.1111/j.1365-2915.1990.tb00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti‐mosquito antibodies on the infectivity of the rodent malaria parasite Plasmodium berghei to Anopheles farauti

Abstract: The effect of mouse anti-mosquito antibodies, present in the bloodmeal, on the infectivity of Plasmodium berghei Vincke to Anopheles farauti Laveran was investigated. Significantly fewer oocysts developed in mosquitoes feeding on mice immunized with sugar-fed mosquito midgut antigens than in mosquitoes feeding on control mice. Mosquitoes feeding on mice immunized with the midgut antigens derived from sugar-fed mosquitoes also showed reduced mortality and had lower infection rates than those fed on unimmunized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…Many problems of identifying suitable protective antigens are common for mosquitoes and ticks. A mosquito vaccine approach could be extremely effective if vector numbers were reduced, and parasite transmission blocked either directly (Lal et al, 1994;Ramasamy and Ramasamy, 1990) or via reducing vector longevity (Billingsley, 1994). Use of purified or partially purified antigens or a combination of antigens may give both a higher death rate and a lower fecundity rate among mosquitoes that feed on specifically sensitized host mammals.…”
Section: Archives Of Insect Biochemistry and Physiologymentioning
confidence: 98%
“…Many problems of identifying suitable protective antigens are common for mosquitoes and ticks. A mosquito vaccine approach could be extremely effective if vector numbers were reduced, and parasite transmission blocked either directly (Lal et al, 1994;Ramasamy and Ramasamy, 1990) or via reducing vector longevity (Billingsley, 1994). Use of purified or partially purified antigens or a combination of antigens may give both a higher death rate and a lower fecundity rate among mosquitoes that feed on specifically sensitized host mammals.…”
Section: Archives Of Insect Biochemistry and Physiologymentioning
confidence: 98%
“…To date, research has focused predominantly on parasite-derived molecules, such as the Pfs25 protein, which is expressed exclusively when the parasite develops in the mosquito midgut and therefore is not under selective pressure in the human host. A few reports documented the feasibility of a TBV based upon mosquito-derived molecules, using whole mosquito midgut extracts to generate transmission-blocking serum, or monoclonal antibodies in various mosquito-Plasmodium systems (7,15,16,19). In addition, it was demonstrated that antibodies that inhibit midgut trypsin activity in Aedes aegypti are capable of blocking the development of the avian parasite Plasmodium gallinaceum, suggesting that mosquito trypsin could be a target for a TBV (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by us and others using polyclonal anti-midgut antibodies have shown inhibition of sporogonic development in the rodent malaria parasite, Plasmodium berghei, and the human malaria parasite, Plasmodium vivax (7)(8)(9). The aim of this study was to: (i) investigate whether mAbs against midgut antigens can block the development of two major human malaria parasites, P. falciparum and P. vivax, in several mosquito species; and (ii) determine whether anti-midgut antibodies reduce mosquito fecundity and survivorship.…”
mentioning
confidence: 99%